Gender and age differences in expression peer violence - Blagojević, Gordana D.; Marjanovic, Bogdan S. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2023)
The complex problem of peer violence has been the subject of many research studies so far.  The prevalence, forms, and manifestation forms of   peer violence, causes, and consequences have been intensively studied. This paper describes and examines the occurrence of violence, considering both gender and age differences. The research has been carried out on a representative sample of 204 pupils of both sexes, in the fifth and eighth grades, who attend two primary schools.   The results of the research show that a greater tendency, towards violent behaviour between boys and girls, has been confirmed (t=5.83, p
Keywords: peer violence; gender differences; age differences; The Peer Violence Questionnaire; elementary school students×